Differences and related physiological mechanisms in effects of ammonium on the invasive plant Xanthium strumarium and its native congener X. sibiricum - Zhang, Zheng; Zhang, Chang; Zhang, Chun-Sha; Wang, Wei-Bin; Feng, Yu-Long (Frontiers in Plant Science, 2022)
Few studies explored the effects of nitrogen forms on exotic plant invasions, and all of them are conducted from the perspective of nitrogen form utilization without considering the effects of ammonium toxicity. The invasive plant Xanthium strumarium prefers to use nitrate, while its native congener X. sibiricum prefers to use ammonium, and the invader is more sensitive to high ammonium based on our preliminary observations. To further reveal the effects of nitrogen forms on invasiveness of X. strumarium, we studied the difference and related mechanisms in sensitivity to ammonium between these species. With increasing ammonium, total biomass, root to shoot ratio and leaf chlorophyll content of X. strumarium decreased, showing ammonium toxicity. For X. sibiricum, however, ammonium toxicity did not occurr. With increasing ammonium, ammonium concentration increased in leaves and roots of X. strumarium, which is associated with the decreased activities of glutamine synthetase and glutamate synthase and the increased ammonium uptake; consequently the contents of hydrogen peroxide and malondialdehyde also increased, which is associated with the decreased contents of reduced glutathione and ascorbic acid. By contrast, X. sibiricum had the abilities to maintain relatively low levels of ammonium, hydrogen peroxide and malondialdehyde in leaves and fine roots, preventing ammonium toxicity. Our results indicate that ammonium accumulation and oxidative damage may be the mechanisms for the ammonium toxicity of X. strumarium, providing a possible explanation that it generally invades nitrate-dominated and disturbed habitats.